The Valuation of Online APE Courses: The Case of Online Consumer Reviews on the Educational Platform - Dubinina, Darya; Manukyan, Ellina; Marchenko, Anastasia; Pilipenko, Ekaterina (Journal of Economic Sociology, 2023)
and the concept of lifelong learning has become increasingly popular in society. At the same time, the use platforms as a new economic organization is growing. It leads to a contradiction between the services’ standardization and the platform’s aim to retain consumers. This has raised the issue of determining the value of online courses as singular goods in terms of quality criteria. The goal of this research is to determine the value of online APE courses for students. A mixed methods research strategy was used, including content analysis of online consumer reviews (N = 300) on the Skillbox website and semi-structured interviews with learners (N = 16). The research found that, in terms of standardization, the singularity of the product is not in its functional utility (core area), but in the additional services (peripheral area) provided by the platform, according to J.-J. Lambin’s multi-attribute product model. As a result, three groups of consumers were identified: promiscuous learners; selective learners focused on additional services (peripheral area) provided by the platform; and selective learners focused on the functional utility (core area) of the educational product. The findings can be applied to the development of digital products on the e-learning market and provide a classification of consumers based on both course selection logics and the top-priority criterion of the product in a platform economy.